Changing Attitude of Consumers from Chemical to Herbal Cosmetics in India - Makkar, Urvashi; Sehra, Amandeep Singh; Tewari, Bhupesh; Rai, Jai Narayan; Rao, Bhagirath; Sharma, Rahul (Indian Journal of Marketing, 2007)
The winds of change in the Cosmetics scenario are blowing forcefully in all parts of the world. India is no exception. The new concept of herbal drugs and cosmetics is the modern rage and we have entered the present century in a climate of confidence and fulfillment. There is a paradigm shift in attitude towards chemical cosmetics. The author in the current research paper attempts to understand the consumption trends with regard to cosmetic products in India. Besides this, an effort has been made to identify the factors because of which consumer attitude and perception are becoming positive towards herbal cosmetics.